Prevalence and Severity of Menopausal Symptoms and the Quality of Life in Middle-aged Women: A Study from Sri Lanka. (1st July 2019) - Rathnayake, Nirmala; Lenora, Janaka; Alwis, Gayani; Lekamwasam, Sarath
Abstract : Menopausal symptoms and quality of life (QOL) of pre- and postmenopausal women in Sri Lanka have not been studied adequately. This study aimed to evaluate the prevalence and severity of menopausal symptoms and the QOL of pre- and postmenopausal women in Galle District, Sri Lanka. A cross-sectional study was conducted with a randomly selected sample of premenopausal (n=184) and postmenopausal (n=166) community-dwelling healthy women aged 30-60 years. The mean (SD) ages of pre- and postmenopausal women, respectively, were 46.1(3.7) and 55.8(3.8) years. Menopausal symptoms were evaluated using the menopause rating scale under three subscales: psychological symptoms, somatovegetative symptoms, and urogenital symptoms. The QOL was evaluated using the short form 36 survey under eight domains. Further, sociodemographic status, gynaecologic factors, physical activity pattern (walking, moderate, and vigorous), body mass index, and waist to hip ratio were also evaluated. The prevalence and severity of all the menopausal symptoms were higher among postmenopausal women. In premenopausal women, the most frequently reported menopausal symptoms were mental exhaustion (49.5%), joint and muscular discomforts (48.5%), and irritability (41.3%). Physical and mental exhaustion (53%), irritability (48.2%), depressive mood (43.4%), and hot flushes (42.2%) were the most frequently reported menopausal symptoms in postmenopausal women. The QOL was significantly impaired among postmenopausal women [mean (SD); 57.47(18.83)] compared to premenopausal women [mean (SD); 66.82(17.93)] (p<0.001). Psychological symptoms score and somatovegetative symptoms score were associated with the QOL of premenopausal women (adjusted R 2 ; 0.35). Somatovegetative symptoms score, psychological symptoms score, moderate and vigorous physical activity scores, and monthly income were associated with the QOL in postmenopausal women (adjusted R 2 ; 0.38). The current study showed that the prevalence and severity of menopausal symptoms and impaired QOL were significantly higher among postmenopausal women, compared to premenopausal women. Menopausal symptoms mostly contributed to the poorer QOL in both pre- and postmenopausal women.